Pengembangan Wawasan Nusantara Sebagai Muatan Pendidikan Kewarganegaraan Generasi Muda Melalui Pemanfaatan Internet - Ariella Prity Anggraini; Fatma Ulfatun Najicha (FKIP, Universitas Palangka Raya, 2022)
The development of archipelago insight as one of the mandatory content of civic education. The archipelango insight becomes an important aspect in the nation as a form of unity. This insight must be implemented by all citizens, especially the younger generation as the successor to the nation's struggle relay. Younger generation as the dominance population of Indonesia affect on the life of nation. Through the archipelago insight as the content Civic Education is expected to create characterful of younger generation. Today’s younger generation can’t be separated from the rapid development of internet and the digitization. This is in accordance with the increasing trend of internet users in Indonesia, with younger generation as main target. The existence of these developments, actualizing the development of understanding the archipelago insight of the younger generation can be done through the internet. This research based on previous studies on the importance of archipelago insight among the younger generation through the use of the internet. The results shows that the development of the archipelago insight of younger generation can be posible through the internet with various alternative ways that can be accessed easily.